MORPHOMETRIC CHARACTERISTICS OF THE VASTUS LATERALIS MUSCLE OF THE QUADRICEPS GROUP OF THE THIGH ACCORDING TO ULTRASOUND RESEARCH - Karatieieva, Svitlana; Honchar, Halyna; Karasievych, Serhii; Ilchenko, Sergiy; Maievskyi, Mykola (Eastern Ukrainian Medical Journal, 2026)
The structure and distribution of muscles play a central role in determining athletic performance, especially in sports involving speed and strength. Objective: To determine the volume of the vastus lateralis muscle (part of the quadriceps femoris) in relation to sports orientation and selection for professional football. Materials and Methods: A total of 48 young men were studied, including 16 players from the Ukrainian professional football team “Universytet” (Chernivtsi), 16 first- and second-year students of the Faculty of Physical Culture, Sports and Rehabilitation at Yuriy Fedkovych Chernivtsi National University, and 16 first- and second-year medical students of Bukovinian State Medical University. All participants underwent morphometric assessment using ultrasound imaging of the vastus lateralis muscle of the quadriceps femoris. Measurements included length, width, and depth. Results: In the upper third of the muscle, the volume in professional football players was 14.3% greater than in students attending football training and 39.3% greater than in control group students. In the middle third, the muscle volume in professional football players was 17.0% greater than in students attending football training and 36.1% greater than in control group students. In the lower third, the volume of the vastus lateralis in professional football players was 19.2% greater than in students attending football training and 44.5% greater than in control group students. Conclusion: Ultrasound examination of the vastus lateralis muscle to determine its volume in the upper, middle, and lower thirds has practical significance for identifying sports orientation and selecting candidates for professional football.